Two new species of caddisflies (Trichoptera: Hydroptilidae, Psychomyiidae) from central and south Spain - González, Marcos A.; Martínez, Jesús; Ruíz, Antonio (Zootaxa, 2013)
In the summer of 2010 and 2011, a large series of caddisflies was collected by the first two authors during a survey of the fauna of Salamanca Province (Central Spain). On closer examination the material revealed a new species of Tinodes, T. felixi sp. n., belonging to a genus relatively well represented in the Iberian fauna, where 12 species have been reported previously (González et al. 1992; González & Martínez 2011).